Sustainable banking implementation in Maybank growth - Tan, Lay Hong (2017)
Sustainability has been applied in banking; not only to satisfy the needs of the existing customers, but also to safeguard the needs of future customers for wealth creation. In Malaysia, some local financial institutions have taken the initiative to embrace sustainability into their banking operations to achieve sustainable competitive advantages. This research studied sustainable banking operating system by Maybank since it is the first sustainability bank in Malaysia. The Gap Model of service quality which developed by Parasuraman et al. (1985), is used in this study to assess the sustainable banking operating system implemented by Maybank. Service quality is largely rooted in the customer’s expectations and perceptions. Literature shows that from prioritizing customer satisfactions at a micro level, the transition has been widening to embed the macro aspects of socioenvironmental responsibility. The research was grounded on social constructivism under an exploratory study. A qualitative case study approach was adopted, backed by three data collection techniques which are semi-structured interviews, observation and document analysis. This research was aimed to investigate the rationales that move Maybank to pursue sustainable banking operating system; Maybank’s roles and responsibilities in implementing in sustainable banking operating system; how far has Maybank implemented the sustainable banking operating system; obstacles faced by Maybank throughout the process of implementing sustainable banking operating system; as well as strategies taken by Maybank to overcome the obstacles identified. After that, explanation building and time-series analysis were adopted for data analysis. The research pointed out Maybank has reached the phase of preventive banking and towards the phase of offensive banking. The bank generally expressed their commitment to move forward with their sustainability goals as they are aware of the increasing expectation of their stakeholders and the society at large. Maybank has adopted two main ways of integrating sustainability into the banking industry. Firstly, the integration of social and environmental responsibility in banking operations through in-house environmental initiatives and socially responsible initiatives. Secondly, the integration of sustainability into its core business through credit risks management, socially responsible investing and philanthropy. It is imperative for other banks in measuring, improving and reporting their sustainability goals and practices as they will eventually be bound to compete on sustainability benchmarking with industry competitors. The government may also need to strengthen its partnership with the banking industry and revisit its regulatory regime in the sector to ascertain the effectiveness of its policy direction in promoting sustainability in the banking industry. Several recommendations for future research can be made: (1) expanding further to include other stakeholders to add some more insights into the sustainable banking practices and (2) further research could relate the sustainable banking with sustainable livelihood of local communities in Malaysia.